Fabric Cutting Table for Homebased Tailor - Ab Hamid, Abdullah Al Rashid; Binti Buseri, Sunurriah; bin Sidek, Ahmad Anwar Safwan (Research in Management of Technology and Business, 2022)
A home-based tailor is someone who does sewing work or takes sewing wages at home. Usually, home-based tailors use the dining table as a place to do the fabric cutting process. This is because to have both a cutting table and a dining table will use a lot of space. Therefore, the general aims of this study are to identify the design criteria, to design and to develop a prototype of fabric cutting table for home-based tailor. Online survey via Google Form used for data gathering to 50 respondents who are home-based tailor and lived in Kota Samarahan, Sarawak. Respondents were asked about demographical data and several closed questions. From data that collect from the survey, specific criteria have been acknowledges for making this fabric cutting table. Among of the criteria is the tabletop for the fabric cutting table must be vinyl laminated, expendable tabletop, and adjustable height. The last criteria is that the fabric cutting table must have 6 drawer.  After finalizing the final design according to data collected, a prototype is build. The protype main material is from plywood and metal. The study show that this research is a success by creating a fabric cutting table with an expendable tabletop and adjustable height that suitable for home-based tailor.